Community Empowerment About Development of Tipang, Tipang Tourism Village Destinations, Baktiraja District, Humbang Hasundutan Regency - Sibarani, Robert; Situmorang, Hamzon; Simanjuntak, Peninna; Lubis, Tasnim; Pardosi, Johnson (Universitas Negeri Medan, 2023)
Village Tipang have potency good natural nor culture that can developed for Becomes destination village tourism in the area Lake Toba. Empowerment Public in development village tour Tipang need conducted remember tourist is very potential commodity for developed . Village tour Tipang have great potential _ for developed in related things _ with component development tour that is attractions culture , accessibility & ancillary ( guide tourism ), amenities , safety and comfort at the destination village tour _ tour tip . Attention to components development tour the will increase number visit tourists to area Lake Toba especially in the village tour tip . because of it is necessary noticed how formation attractions culture from tradition based culture _ wisdom local , development accessibility and ancillary ( guide travel ) with empower Public village tour What are the tips and strategies needed ? done so that the village tour Tipang Becomes destination more travel _ good from side amenities , safety and comfort . There is four priority devotion community activities carried out in the Village tour Tipang this namely : forming group attractions culture based wisdom local , develop accessibility and ancillary ( guide travel ) with empowerment community , develop amenities , facilities and infrastructure facility support , develop quality safety and comfort destination village tour _ tour Lean and empower Public for increase economy with stage discussion and training . Activity devotion this expected capable fix and improve level economy people in the village tour tip.